Effect of Bone Marrow and Adipose Mesenchymal Stem Cells on Rat Intestinal Injury Induced by Methotrexate - Marwa A. Masoud; Eman G. Mohamed; Wedad A. Hassan; Ebtehal Mohammad F (Journal of Tissue Repair and Regeneration, 2018)
Methotrexate (MTX) is an anti-metabolite in cancer chemotherapy and is associated with various toxicities assigned to inflammation and oxidative stress. The present study was undertaken to corroborate the therapeutic effects of bone marrow mesenchymal stem cells (BM-MSCs) and adipose-derived mesenchymal stem cells (AD-MSCs) in MTX-induced intestinal toxicity in experimental animals as compared with dexamethasone (Dex). Rats were divided into five groups: I-Normal control group, II- MTX (14 mg/kg, as a single dose/week for 2 weeks), III & IV- BM-MSCs & AD-MSCs (2 × 106 cells/rat, 1 week after last dose of MTX), respectively, plus V- Dex (0.5 mg/kg/ for 7 days, 1 week after last dose of MTX). MTX induced marked intestinal elevation of interleukin-6, total oxidant, and nitrite/ nitrate, caspase-3 contents and myeloperoxidase activity, along with the reduction of reduced glutathione content and catalase activity. In conclusion, the positive modulation of MTX toxicity could be attributed to the free radical scavenging, anti-inflammatory and antiapoptotic potential of BM-MSC and AD-MSCs which will possibly make them as remarkable hopeful for the treatment of intestinal injury.
Keywords: Intestinal Injury